Formation Capital Character Reason Critical on Subjects Pancasila in Schools Base Post Gen Z Based - Magtublo, Rulia AR; Santoso, Gunawan (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This research aims to explore the capital for building critical reasoning character in post-Gen Z generation students through learning Pancasila subjects in elementary schools. The main focus is to understand how Pancasila values can be integrated and understood in the context of the lives of today's students who tend to be influenced by technology and social media. Design/methodology/approach: The research methods used include literature studies and analysis of the development of the characteristics of the post-Gen Z generation, as well as effective learning strategies in increasing their understanding of moral, ethical and democratic values. Findings: It is hoped that the results of this research can contribute to designing a relevant and effective curriculum to shape students' critical reasoning character in this digital era. Paper type: Research paper.